Experimental investigation of dynamic pressure loads during dam break - Lobovský, L.; Botia-Vera, E.; Castellana, F.; Mas-Soler, J.; Souto-Iglesias, A. (Journal of fluids and structures, 2014)
The objective of this research work has been to conduct experimental measurements on a dam break flow over a horizontal dry bed in order to provide a detailed insight, with emphasis on the pressure loads, into the dynamics of the dam break wave impacting a vertical wall downstream the dam. The experimental setup is described in detail, comprising state of the art miniaturized pressure sensors, high sampling rate data acquisition systems and high frame-rate video camera. It is a 1:2 scale of the highly cited (Lee et al., 2002, Journal of Fluids Engineering, 124) article experimental apparatus. Kinematics has been analyzed focusing on the free surface and wave front evolution. Experimental observations regarding liquid height and wave front speed have found to be in agreement with existing literature. This agreement enables the authors, assuming a similar framework, to discuss the measured pressure loads as a consequence of the dam break wave front impacting on the downstream wall. These loads show a substantial variability which has been statistically characterized. The measured quantities have been compared with the scarce available data in the literature, whose consistency is discussed. Measurements have been conducted with two filling heights. Scaling effects for such heights are also analyzed. As a direct result of the present initiative, an extensive set of data for computational tools validation is provided as Supplementary Materials, including pressure signals, wave height measurements and experimental videos. •Dam break on dry bed experiment series for 2 filling heights is discussed in detail.•Flow kinematics is analyzed and compared with the literature.•Statistical analysis of pressure loads, rise–decay times and impulses is provided.•Pressure vs. dam-break filling height does not follow a linear trend.•Measurements conducted with off-centered pressure sensor to assess 3D dynamics.